2021
DOI: 10.1002/biot.202100059
|View full text |Cite
|
Sign up to set email alerts
|

Heterologous expression of cyanobacterial gas vesicle proteins in Saccharomyces cerevisiae

Abstract: Given the potential applications of gas vesicles (GVs) in multiple fields including antigen-displaying and imaging, heterologous reconstitution of synthetic GVs is an attractive and interesting study that has translational potential. Here, we attempted to express and assemble GV proteins (GVPs) into GVs using the model eukaryotic organism Saccharomyces cerevisiae. We first selected and expressed two core structural proteins, GvpA and GvpC from cyanobacteria Anabaena flos-aquae and Planktothrix rubescens, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…GvpF is the primary binding partner of GvpB (Figures 4D & 5A), an interaction that is superseded by the secondary binding of GvpG (Figures 3C & 5B). We propose that GvpF and GvpG are the chaperones of GvpB and prevent it from becoming thermodynamically trapped and forming proteotoxic amyloid species 43,54 . GvpF was observed to bind the first α-helix of haloarchaeal shell protein GvpA 41 , supporting a co-translational chaperoning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GvpF is the primary binding partner of GvpB (Figures 4D & 5A), an interaction that is superseded by the secondary binding of GvpG (Figures 3C & 5B). We propose that GvpF and GvpG are the chaperones of GvpB and prevent it from becoming thermodynamically trapped and forming proteotoxic amyloid species 43,54 . GvpF was observed to bind the first α-helix of haloarchaeal shell protein GvpA 41 , supporting a co-translational chaperoning.…”
Section: Discussionmentioning
confidence: 99%
“…First, we hypothesized that the number of E. coli transformants may reflect the cellular burden of the GV proteins being expressed, since leaky expression can still occur without chemical induction during the growth of cells on agar plates. Among GV proteins, the major shell protein, GvpB, has a highly hydrophobic surface, which is known to cause aggregation and proteotoxicity 43 . Indeed, we observed that every transformation that included expression of a fusion protein of GvpB led to a decrease in the total number of transformants (Figure 6A and Table S3).…”
Section: Datasets On Cellular Burden Protein Expression and Tolerance...mentioning
confidence: 99%
“…There are also many prokaryotic organelles, such as gas vesicles, that have been artificially constructed in engineered strains such as Halobacterium salinarum , Escherichia coli, and Saccharomyces cerevisiae . Many synthetic scaffolds, such as nucleic acid interaction partners and protein interaction partners, have been developed to shorten the distance between enzymes by forming substrate delivery microcompartments and act as a controllable tool for constructing ASCs to promote the synthesis of target products . Since these ASCs have not been extensively exploited to promote metabolic synthesis in MCFs, we will not review them extensively here.…”
Section: Designing Artificial Subcellular Compartments To Enhance The...mentioning
confidence: 99%
“…For time course experiments, culture samples were collected every 12 h to determine the SBCFA levels and cell density (OD 600 ) was measured by a spectrophotometer BioPhotometer Plus (Eppendorf, Germany). The culture samples were diluted by SCD-U with KPB to adjust the cell concentration and the fluorescence intensity was measured on a Synergy H1 microplate reader and normalized to the cell density (Jung et al, 2021) as described above.…”
Section: Detection Of Intracellularly Produced Sbcfas By the Sbcfa Bi...mentioning
confidence: 99%